Prognostic relevance of sleep apnea syndrome in patients with pulmonary arterial hypertension. (25th November 2020) - Precek, J; Vykoupil, K; Kovacik, F; Hutyra, M
Abstract: Introduction: Sleep disordered breathing (SDB) is a group of ventilatory disorders during sleep which includes obstructive sleep apnea (OSA), central sleep apnea (CSA), and sleep related hypoventilation. In patients with SDB, the prevalence of pulmonary hypertension (PH) ranges from 17% to 52%. While SDB is prevalent in the general population with recent estimates of 20% to 30%, in those with cardiovascular disease, particularly left ventricular failure, there is a higher reported prevalence of 47%. Aims: The aims of this study were to determine the prevalence and prognostic relevance of sleep apnea in a cohort of patients with newly diagnosed pulmonary arterial hypertension (ESC/WHO Group 1 pulmonary hypertension). Methods: We evaluated prospectively 76 patients with the pulmonary arterial hypertension (mean age 54±16 years; 45% male). All patients underwent right heart catheterisation, clinical assessments, sleep study, standard laboratory testing and evaluation of subjective sleepiness by the Epworth Sleepiness Scale. Sleep test was provided with an ApneaLink Plus, consisting of nasal pressure sensor, respiratory effort band, and pulse oximeter worn on the finger. Subjects previously treated for or diagnosed with SDB were excluded from the study. Results: Sleep apnea (SA) – defined as apnea-hypopnea index (AHI) ≥5/h – was found in 59 (77.6%) of the pulmonary arterial hypertension (PAH) patients. Mean AHI in the cohort of PAH patients with SA was 26.1±16.6/h. Mean follow-up was 24 months, during which 15 (19.7%) patients died. Characteristics of parameters related to SA in groups of survivors and deceased are in table 1. From the sleep apnea-related parameters, only time with O2Sat <90% – T90 was significantly associated with mortality (AUC 0.856; 95% CI 0.693 – 1.019; p<0.001). Conclusions: The presence of sleep apnea in pulmonary arterial hypertension patients is high. The prevalence of sleep apnea is higher in PAH patients than in the general population. The presence of sleep apnea in patients with PAH was not associated with worse prognosis, but noctural hypoxemia (time with O2Sat <90%) was related to poor prognosis. Sleep apnea in patients with PAH should be screened for systematically. Funding Acknowledgement: Type of funding source: None